The role of psychological factors in the alpine skiing learning process of the ski beginners - Cigrovski, Vjekoslav; Matković, Bojan; Matković, Branka; Ivanec, Dragutin (2007)
The role that psychological factors play in influencing sport in general has reached great attention in current sports literature. In the present study the influence of fear, self-efficacy and worry on different learning methods in the alpine skiing-na&iuml ; ; ve young people was investigated. 126 students of the physical education, with no previous knowledge of alpine skiing entered the study. They were aged 23.3&plusmn ; ; 1.66 years, 96 of them were male and 30 were females. After completing the three questionnaires (Penn State Worry Questionnaire, Self-efficacy and Fear questionnaire) they were randomly assigned to two equally-sized groups. The groups differed only in a method used to learn alpine skiing. The learning process lasted 7 days for both groups, after which the participants were graded 1 to 5 according to the demonstrated knowledge of five chosen elements. The examined psychological factors did not correlate significantly with the level of the alpine skiing knowledge neither in the control nor in the experimental group. Although participants of the experimental and control group differed significantly in the level of the learned alpine skiing measured through grades obtained for the elements one turn, short turn and parallel turn (p=0.03, p=0.01 and p=0.01 respectively), the difference seems not be influenced by the psychological factors. The results of the study were interesting in respect to popularity of alpine skiing. The examined emotions did not affect the learning process adversely, so it seems that worry, self-efficacy and fear were not the psychological barrier preventing the successful learning of alpine skiing in neither experimental nor control group.
Projekt MZOS
Projekt MZOS
Projekt MZOS
ENG